Influence of Facial Symmetry in Mate Choice - Portales Rosas, Katherine; Gil Burmann, Carlos; Beltrami Boisset, Marcial (Revista de Psicología, 2009)
Many studies suggest that the facial symmetry, as indicator of stability in the development and individual´s health, influence the evaluation of the characteristics of the pair. To determine the importance of facial symmetry in mate choice, we have applied questionnaires in diverse public space of Santiago de Chile to 718 heterosexual people: 456 women and 262 men. They had to evaluate three images of faces of people of the opposite sex with different levels of facial symmetry. We concluded that the facial symmetry influences the evaluation of the pair´s characteristics but, in addition to the symmetry, other factors like the use of artificial beauty products can be more important phenotypic signals than facial symmetry.